The Brain drain: what do we know? - Docquier, Frederic; Sekkat, Khalid (Paris Agence Francaise de Developpement, Departement de la Recherche, 2006)
Is the brain drain a curse or a boon for developing countries? In the face of it, what are the policy options open to international organizations and home country governments? This paper reviews what is known to date about the magnitude of the brain drain from developing to developed countries and the way such skilled migration affects the source country. In a first, descriptive section, we characterize the determinants, evolution and spatial distribution of the brain drain. We distinguish several measures based on education attainment, age of entry and occupation. We then review the traditional literature and explain why the brain is a major issue of concern for origin countries. Section 3 provides a theoretical and empirical discussion of the various channels through which the brain drain positively impacts on sending countries. Finally, we discuss the implications for migration, education and taxation policies. .
Abstract / Resume -- Introduction -- How important is the brain drain -- The determinants of the brain drain -- Measuring the brain drain: methodology -- issues -- How big is the brain drain -- Emigration by occupation - medical brain -- drain -- Should we eliminate the brain drain -- Brain drain, human capital and -- growth -- Ex-ante human capital formation -- Remittances - Return migration -- Diaspora externalities -- Governcance and corruption -- Summary -- Policy -- discussion -- Immigration policy -- Education policy -- At the agenda
Includes bibliographical references (p. 30)
Keywords: Labour market; LABOUR MOBILITY; BRAIN DRAIN; INTERNATIONAL MIGRATION; LABOUR MIGRATION